Cloud Computing Security Issues and Existing Solutions - Vasisth Roy; Chaitanya Deshpande; Nikesh Kumar; Dr. Mahendra Suryavanshi (Vidhyayana - An International Multidisciplinary Peer-Reviewed E-Journal - ISSN 2454-8596, 2023)
Cloud computing benefits both the service providers and end-users by offering enhanced accessibility, reduced IT maintenance burdens, scalable infrastructure, and cost-effective services. Cloud computing technology has several issues such as security, service reliability, vendor lock-in, data lock-in, load balancing, in cast, lack of transparency, resource allocation, interoperability. Security issues in cloud computing arise due to several parameters such as the shared infrastructure, weak access controls, data confidentiality, integrity, availability, and compliance with regulations. In this paper, existing solutions to mitigate cloud security issue are analyzed.